Evaluation of a Simple Antibiotic-Free Cryopreservation Protocol for Drone Semen - Sophie Egyptien; Jérôme Ponthier; Fabien Ectors; Brice Thibaut; Stéfan Deleuze (Insects)
The increasing reliance of modern agriculture on honey bee (Apis mellifera) pollination has driven efforts to preserve and enhance bee populations. The cryopreservation of drone semen presents a promising solution for preserving genetic diversity and supporting breeding programs without live animal transport risks. This study aimed to evaluate a one-step dilution antibiotic-free drone semen slow-freezing protocol under field conditions with in vitro and in vivo parameters. Semen viability was tested by two different mixes of dyes, and both techniques gave similar results, showing a post-thaw viability drop of 37%. Virgin queens were inseminated either with fresh or frozen–thawed semen. Survival rates until egg-laying onset and female brood production were similar for both groups; however, colonies with queens inseminated with fresh semen were more likely to go into wintering. Results suggest that frozen–thawed semen can support viable queen insemination, with potential for female brood production even without antibiotics in the diluent. This study highlights the need for further refinement of cryopreservation protocols, particularly regarding semen quality and queen longevity, to improve the feasibility of cryobanking for Apis mellifera conservation and breeding.